Does mean arterial pressure augmentation improve neurological recovery of blunt spinal cord injuries: an EAST multicenter trial - Jeffry Nahmias; Ryan Peter Dumas; Brian Daley; Dalier R Mederos; Bradley M Dennis; Michael Steven Farrell; Stephanie Scott; Gregory Schaefer; Asanthi Ratnasekera; Alison Smith; Scott Armen; Joshua Hill; et al. (Trauma Surgery & Acute Care Open)
Background Treatment of blunt traumatic spinal cord injuries (SCIs) often includes maintaining elevated mean arterial blood pressures (MAP) to enhance perfusion to the spinal cord. Optimal hyperperfusion protocols and treatment algorithms have yet to be delineated due to a paucity of large volume prospective studies. This study aims to identify predictors of neurological improvement in American Spinal Injury Association (ASIA) impairment score following blunt SCI.Study design Prospective (January 10, 2021 to June 1, 2023) multicenter study included blunt SCI patients age >18 with complete neurological examination documented on hospital arrival. Patients were divided into two groups: neurological improvement and no improvement, based on their change in ASIA score from arrival to hospital discharge.Results A total of 19 centers contributed 222 patients of those, 164 had pre-ASIA and post-ASIA scores. The ASIA improvement group had 36 patients (22%). There was no statistical difference in the median percentage of time patients spent at a MAP >85 mm Hg during treatment 80.7% (IQR 63.6, 93.4) no improvement vs 83.6% (IQR 70.1, 93.0) in the improvement, (p=0.87). There was no difference in the median duration of MAP treatment in hours between the groups (95.6 hours (IQR 62.55, 113.48) in the no improvement group versus 96 (IQR 72, 113.5) (p=0.40) in the improvement group).Conclusions Overall, 22% of all blunt SCI patients saw an improvement in their ASIA score. Adherence to and length of MAP augmentation was not a statistically significantly different between groups.Level of evidence Level IV Therapeutic/Care Management.